2022
DOI: 10.2169/internalmedicine.7664-21
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Pollen-food Allergy Syndrome Allergologically in a Patient with Suspected Eosinophilic Gastroenteritis

Abstract: Pollen-food allergy syndrome (PFAS) consists of type I allergy to pollen and multiple food items that are cross-reactive to the pollen. PFAS typically occurs in the oral cavity and can co-occur with eosinophilic esophagitis. However, it is infrequently reported to present with symptoms of eosinophilic gastroenteritis (EGE), such as abdominal pain and eosinophilic infiltration of the gastrointestinal tract. We herein report a patient with a condition initially suspected of being EGE based on symptoms and pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In one study, PFAS was identified in 26% of patients with eosinophilic esophagitis [ 6 ]. However, only a few cases of eosinophilic gastroenteritis in patients with PFAS have been reported [ 7 , 8 ]. Soybean allergens are known to induce systemic symptoms in individuals with PFAS, likely because of their intrinsic molecular stability [ 5 ].…”
mentioning
confidence: 99%
“…In one study, PFAS was identified in 26% of patients with eosinophilic esophagitis [ 6 ]. However, only a few cases of eosinophilic gastroenteritis in patients with PFAS have been reported [ 7 , 8 ]. Soybean allergens are known to induce systemic symptoms in individuals with PFAS, likely because of their intrinsic molecular stability [ 5 ].…”
mentioning
confidence: 99%